Downward nominal wage rigidity and macroeconomic adjustment in a monetary union - Fagan, Gabriel (Trinity College (Dublin, Ireland). Department of Economics, 2014)
The core of this thesis consists of three papers. Although independent, a common theme running through the papers is the macroeconomic adjustment of an open economy in a monetary union. In particular, we look at how adjustment to shocks is affected by two factors: downward nominal wage rigidity (DNWR) and central bank financing in a monetary union. The analysis in the papers combines of the use of of empirical data and estimation with the simulation of microfounded dynamic general equilibrium models.
Keywords: Economics, Ph.D.; Ph.D. Trinity College Dublin